Case Report: Unusual oral cavity changes associated with methamphetamine abuse - Skrypnyk, Maksym; Skrypnyk, Roman; Petrushanko, Tatiana; Skikevych, Margarita; Petrushanko, Vladymyr; Skrypnyk, Igor (Frontiers in Public Health, 2025)
Methamphetamine abuse is a growing global health concern, recognized for its highly addictive properties and severe effects on the human body. Commonly referred to as crystal, chalk, or ice, methamphetamine is a synthetic stimulant that can be administered in various ways. Methamphetamine abuse is associated with a spectrum of oral health issues known as “meth mouth,” including rampant teeth caries, extensive occlusal tooth wear, periodontal diseases, xerostomia, bruxism, and poor oral hygiene. Despite the significant oral health impact, the exact pathogenesis remains unclear due to the limited number of reported cases and comprehensive studies performed. This case series details changes in oral and general health of different severity associated with methamphetamine abuse, highlighting unusual presentations such as the generalized decrease in teeth sensitivity, which can be associated with aseptic tooth pulp necrosis, hairy black tongue, rampant arrested caries, decreased periodontal inflammation, specific sunflower seed abrasions on antagonistic central incisors, pityriasis rosea skin lesion and palmar erythema. The clinical management was presented in detail and justified, which entails conservative dental, periodontal and oral mucosae treatments and highlighted the need for a comprehensive complex examination of these patients and financial consideration in treatment planning. This case series underscores the need to recognize the diverse oral and general health effects of methamphetamine abuse, which vary with duration and individual symptoms. Patients often withhold substance use, leading to delayed diagnosis until severe manifestations arise. Enhanced awareness among healthcare providers can improve diagnosis and management, offering valuable insights into underlying mechanisms and enabling better care for this high-risk population.